Dignity in Transgender Lives: A Capabilities Approach. Issue 1 (2nd January 2020) - Reed, Ryan
Abstract: Transgender people frequently contend with serious challenges to living lives of dignity. They face elevated risks of violent assault, discrimination in employment and healthcare, and social, legal, and political hostility. This paper considers Martha C. Nussbaum's capabilities approach as a means of addressing the needs of transgender people. Following Nussbaum's lead, the analysis considers how the capabilities approach speaks to the disparities and obstacles faced by transgender people and which of Nussbaum's list of Central Capabilities must be secured to ensure that they are able to live flourishing lives of dignity. Further, the paper advances proposals to modify three of the Central Capabilities in order to comprehensively address the dignity needs of transgender people and, more broadly, all persons whose gender presentation does not conform to traditional expectations.